Characterizing the properties of asphalt concrete (AC) at different testing conditions and loading modes by different testing methods and samples (SCB, ENDB and DCT): A comparative review of fracture parameters - Aliha, M. R. M.; Ghoreishi, S. M. N.; Shaker, Hamid; Jafari, Faezeh; Bazoobandi, Payam; Sadowski, Tomasz; Choupani, Naghdali (Elsevier Sci Ltd, 2025)
Numerous researchers have employed different specimens, such as Semi-Circular Bend (SCB), Edge Notched Disc Bend (ENDB), and Disc Compact Tension (DCT) specimens for fracture toughness and fracture energy measurement of asphalt concrete (AC) materials. Such studies aim to investigate various measurement methods applied for different types of loading, fracture modes (basic modes I, II, III and combined modes I-II and I-III), and environmental and testing conditions (e.g., temperature or mixture type) to assess the cracking resistance of AC composites and pavements. This review compares various measurement devices, specimens and approaches regarding their specific applications, advantages, and disadvantages of the available fracture toughness testing methods and specimens. The influence of different affecting parameters, including temperature, aggregate type, bitumen type and percentage, additives such as fibers, porosity, air void amount, size and type of aggregate, freeze-thaw cycles, and compaction techniques on the fracture behavior of AC mixtures is reviewed.
Keywords: Fracture toughness; Fracture energy; Measuring methods; Asphalt mixture; SCB; ENDB; DCT specimens; Influence of geometrical, mixed modes loading and environmental conditions